Children's Constitutional Rights: Past, Present and Yet to Come - Brady, Alan (My University, 2018)
The entry into force of Article 42A of the Constitution on 28 April 2015 was a significant event. However, the nature of that significance has yet to be fully understood. Article 42A is, in constitutional terms, an extremely new provision and so its role will only become clear as it is interpreted and applied by the Superior Courts. This is true of all constitutional provisions, but most of the Fundamental Rights provisions in the 1937 Constitution have been in place for eight decades and so there has been more opportunity to ascertain their meaning. This paper examines the constitutional rights enjoyed by children as children. It does so in four parts. The first part explores the way in which children’s rights were developed as unenumerated rights prior to the entry into force of Article 42A. The second part examines some of the initial developments under Article 42A. The third part examines the potential impact of Article 42A in the specific area of homelessness and housing. The fourth part raises some preliminary questions about children’s rights in the constitutional order, particularly as they relate to socio-economic rights.
Catherine McGuinness Fellowship Seminar: Children and Article 42A of the Irish Constitution